A discontinuous nonlinear singular elliptic problem with the fractional rho-Laplacian - Zineddaine, Ghizlane; Sabiry, Abdelaziz; Kassidi, Abderrazak; Chadli, Lalla Saadia (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, we use the topological degree method, based on the abstract Hammerstein equation, to investigate the existence of weak solutions for a certain class of elliptic Dirichlet boundary value problems. These problems involve the fractional ρ-Laplacian operator and involve discontinuous nonlinearities in the framework of fractional Sobolev spaces.
Keywords: discontinuous nonlinearities; Hardy potential; fractional rho-Laplacian; weak solution; topological degree theory